A Practical and General Amidation Method from Isocyanates Enabled by Flow Technology. (17th August 2018) - Williams, Jason D.; Kerr, William J.; Leach, Stuart G.; Lindsay, David M.
Abstract: The addition of carbon nucleophiles to isocyanates represents a conceptually flexible and efficient approach to the preparation of amides. This general synthetic strategy has, however, been relatively underutilized owing to narrow substrate tolerance and the requirement for less favourable reaction conditions. Herein, we disclose a high‐yielding, mass‐efficient, and scalable method with appreciable functional group tolerance for the formation of amides by reaction of Grignard reagents with isocyanates. Through the application of flow chemistry and the use of substoichiometric amounts of CuBr2, this process has been developed to encompass a broad range of substrates, including reactants found to be incompatible with previously published procedures.